V pričakovanju e-zdravja - Ramšak, Mojca (Etnolog. Nova vrsta (Ljubljana), 2011)
E-health is the field of medical information technology that refers to the use of electronic/digital processes in the prevention, diagnostics, treatment and monitoring of diseases, people's decisions about their health and ways of living, and the provision of information through the Internet. At present, e-health is thus still nearly synonymous with the information and communication technologies in health care, which Slovenia is not yet able to cope with in terms of technology, organisation, legislation, and ethics. Precisely because only some segments in some health institutions are operational in the system of e-health (e.g. electronic waiting lists, electronic referrals, digital data transfers, paperless diagnostics, and the production of classical X-Ray images), it is worth keeping in mind that along with the necessary technological advance we should equally improve the values of safe, accessible, quality, and sensible treatment and cooperation between health workers and patients.
Keywords: medical anthropology; Slovenci; Slovenes; ethics; e-zdravje; information technology; internet; society; medicinska antropologija; etika; informacijska tehnologija; družba; e-health